JADIDISM IS ETERNAL SCIENCE IN THE MEMORY OF GENERATIONS (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
The Jadid movement is an expression of scientific and philosophical enlightenment. We considered it necessary in this article to shed light on the socio-philosophical features of the Enlightenment and the enlightenment movement or Jadidism.